Mathematics achievement and self-efficacy: Relations with motivation for mathematics. (2015) - Skaalvik, Einar M.; Federici, Roger A.; Klassen, Robert M.
Highlights: Math self-efficacy strongly predicted intrinsic motivation and persistence in math. Self-efficacy also predicted effort and help-seeking behavior. Teacher support predicted both self-efficacy and all measures of motivation. Math grades were indirectly related to the motivational constructs. The indirect relations were mediated through teacher support and self-efficacy. Abstract: In this study we analyzed if teacher support and student self-efficacy mediated the relations between students' grades in mathematics and different measures of mathematics motivation. Participants in the study were 823 Norwegian middle school students. Indicators of motivation were intrinsic motivation, effort, persistence, and help-seeking behavior. Data were analyzed by means of multiple regression and SEM analysis. The relations between students' grades and motivation were partly mediated through emotional support and self-efficacy.